Liver Fibrogenesis in Non-Alcoholic Steatohepatitis - Ma, Xiong (Frontiers in Physiology, 2012)
Nonalcoholic fatty liver disease (NAFLD) is emerging as one of the most common chronic liver diseases in developed Western countries. Nonalcoholic steatohepatitis (NASH) is the most severe form of NAFLD, and can progress to more severe forms of liver disease, including fibrosis, cirrhosis, and even hepatocellular carcinoma. The activation of hepatic stellate cells plays a critical role in NASH-related fibrogenesis. Multiple factors, such as insulin resistance, oxidative stress, proinflammatory cytokines and adipokines, and innate immune responses, are known to contribute to the development of NASH-related fibrogenesis. Furthermore, these factors may share synergistic interactions, which could contribute to the process of liver fibrosis. Given the complex etiology of NASH, combined treatment regimes that target these different factors provide potential treatment strategies for NASH-related liver fibrosis.